PERBEDAAN SISTEM BUNYI DAN KOSAKATA BAHASA MINANGKABAU DI KENAGARIAN KAMBANG UTARA KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN DENGAN BAHASA MINANGKABAU UMUM - Sutia, Trisna; Agustina, Agustina; Manaf, Ngusman Abdul (Universitas Negeri Padang, 2017)
This study was conducted to describe: (1) The difference in pronounce system and a vocabulary of Minangkabau in Northern Kambang sub- district,Â Lengayang Distric,Â of South Coastal Regency with General Minangkabau language. (2) the difference in the vocabulary of Minangkabau language in Northern Kambang sub-district,Â Lengayang District,Â of South Coastal RegencyÂ with General Minangkabau language. The research is a qualitative study by using descriptive methods. Data were collected through a technical conversation with native speakers in North Kambang sub-district.Â Analyzing data is carried out with the following steps. First, transcribe the informantsâ€™ speech thatÂ have been recorded. Second, classifying the data of vocabulary differences in the pronounce system. Thirdly, concludes the different data based on the data that has been analyzed. Based on the results of the study, concluded the following. First, the differences in sound system of Minangkabau language in Northern Kambang sub-district, Lengayang District, South Coastal regency with the general Minangkabau language include: (1) the difference vocals consist of differences in vowel (a - u), (e - i), and ( i - a), (2) differences in the consonants made up the difference consonants (Ã¸ - h), (m - b), (n - Ã¸), (Ã¸ - n), (Î· - Ã¸), (Î· - n),Â (n - Ã¸), (n - n), (r - Ã¸), (Ã¸ - r), (Ê - h), (Ê - r), (s - h), (w - Ã¸), (w - r), and (y - Ã¸), (3) the diphthong consists of the difference diphthongs (É› - É›a), (u - ua), and (ur - ua), Second, the differences in Minangkabauâ€™s vocabularies in Northern Kambang sub-district, Lengayang District,Â South CoastalÂ regency withÂ the general Minangkabau language occur in: (a) verb, (b ) adjective, and (c) nouns.Keywords: phonology, sound system, vocabulary, minangkabau language